2019
DOI: 10.1044/2019_ajslp-16-0147
|View full text |Cite
|
Sign up to set email alerts
|

Speech-Language Disorders in 22q11.2 Deletion Syndrome: Best Practices for Diagnosis and Management

Abstract: Purpose Speech and language disorders are hallmark features of 22q11.2 deletion syndrome (22qDS). Learning disabilities, cognitive deficits, palate abnormalities, velopharyngeal dysfunction, behavioral differences, and various medical and psychiatric conditions are also major features of this syndrome. The goal of this document is to summarize the state of the art of current clinical and scientific knowledge regarding 22qDS for speech-language pathologists (SLPs) and provide recommendations for cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 87 publications
1
51
0
Order By: Relevance
“…Development delays need to be checked at every step of infancy and childhood, as early intervention can help provide support for children with the deletion [ 69 , 70 ]. The most common problems are motor delays and speech difficulty, which can be connected with very frequent conductive hearing impairment (HP:0000405) and muscular hypotonia (HP:0001252) [ 61 , 71 , 72 , 73 , 74 ]. Delays in reaching motor milestones and the emergence of language are common in children with 22q11.2DS.…”
Section: Individual Levelmentioning
confidence: 99%
“…Development delays need to be checked at every step of infancy and childhood, as early intervention can help provide support for children with the deletion [ 69 , 70 ]. The most common problems are motor delays and speech difficulty, which can be connected with very frequent conductive hearing impairment (HP:0000405) and muscular hypotonia (HP:0001252) [ 61 , 71 , 72 , 73 , 74 ]. Delays in reaching motor milestones and the emergence of language are common in children with 22q11.2DS.…”
Section: Individual Levelmentioning
confidence: 99%
“…A significantly increased risk for comorbidities (e.g. psychiatric disorder, intellectual disability, language disorder, autism spectrum disorder, psychotic disorder, attention deficit/hyperactivity disorder) was found in a large Swedish register cohort study on children with orofacial clefts (Tillman et al, 2018 Márquez-Ávila et al, 2015;Persson, Lohmander, Jönsson, Óskarsdóttir, & Söderpalm, 2003;Solot et al, 2019), so that a substantial proportion of children with 22q11.2DS present with a cleft and CAS. Furthermore, there have been reports of submucous clefts being found when patients are assessed for suspected CAS (Murray et al, 2015) and…”
Section: Cleft Palate ± Lip and Comorbiditymentioning
confidence: 99%
“…It has been suggested that intraoral structural indicators of SMCP should be identified as early as possible in the 22q DS population, with the recommendation of early initiation of speech sound intervention and a warning that lack of typical stigmata does not rule out possible occult SMCP (Solot et al, 2019). Early identification and initiation of speech therapy is recommended for this patient population and may be even more important in patients that will require SMCP repair.…”
Section: Discussionmentioning
confidence: 99%